Scalable Perceptual and Lossless Audio Compression Based on MPEG-4 AAC - Geiger, Ralf; Schuller, Gerald; Herre, Jürgen; Sperschneider, Ralph; Sporer, Thomas (115th AES Convention, 2003)
This paper presents a scalable lossless enhancement of MPEG-4 Advanced Audio Coding (AAC). Scalability is achieved in the frequency domain using the Integer Modified Discrete Cosine Transform (IntMDCT), which is an integer approximation of the MDCT providing perfect reconstruction. With this transform, and only minor extension of the bitstream syntax, the MPEG-4 AAC Scalable codec can be extended to a lossless operation. The system provides bit-exact reconstruction of the input signal independent of the implementation accuracy of the AAC core coder. Furthermore, scalability in sampling rate and reconstruction word length is supported.<br
herre_papers_perceptual_audio_coding